Integration of Mobile and Web Applications to Prevent Crime - Barrionuevo, Elvis; Ticona, Wilfredo (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Citizen insecurity and crime represent one of the greatest challenges, as they affect people’s peace of mind and perception of security. Crime prevention and emergency management face challenges due to the lack of effective mechanisms for collecting and managing information, which hinder decision-making and affect the effectiveness of measures to combat crime. Therefore, the implementation of mobile and web applications is intended to reduce the risk of crime by supporting daily data collection, strategy planning, crime monitoring, diagnosis of the current situation, and coordination and evaluation of the competencies of citizen security agents. The SCRUM framework was applied to address the development and implementation of the model, considering all phases and artifacts. The results demonstrate that the implementation of mobile and web applications significantly supports crime prevention and strengthens district citizen security.